402. Spontaneous pneumothorax in COVID-19. (31st December 2020) - Tariq, Zain; Doeing, Diana; Nauriyal, Varidhi; Chaudhry, Zohra Sarfraz; Shallal, Anita; Bhargava, Pallavi; Chen, Anne; Ramesh, Mayur; Herc, Erica
Abstract: Background: Pneumothorax has been reported with the use of positive pressure ventilation in COVID-19 pneumonia. Literature on spontaneous pneumothorax (PTX) in COVID-19 patients is scant. We present a case series of 7 patients with COVID-19 pneumonia, who developed spontaneous pneumothorax without prior mechanical ventilation. Methods: A retrospective chart review of 7 cases was performed from two different hospitals in the US between 4/6/2020–5/15/2020. Hospitalized patients with confirmed COVID-19 by nasopharyngeal RT-PCR who developed spontaneous pneumothorax were included. Collected data included demographics, co-morbidities, inflammatory biomarkers, chest imaging and management strategies. Length of stay, transfer to intensive care unit and death were the assessed outcomes. A descriptive analysis was done. Results: There were 3 patients from Henry Ford Health System, Michigan and 4 patients from Silver Cross Hospital, Illinois. Median age was 75 years and 6 out of 7 (85.7%) were males (Table 1). There were no co-morbidities associated with spontaneous pneumothorax except for one patient with COPD. None of the patients' imaging prior to diagnosis of pneumothorax revealed any underlying blebs. Median time from symptom onset to diagnosis of pneumothorax was 17 days. One of the patients had tension pneumothorax, two had bilateral pneumothorax and three had pneumomediastinum (Figure 1). Four patients required chest tube placement, three required escalation to ICU, of which two died. Table 1. Demographics and Clinical Characteristics of Patients with Spontaneous Pneumothorax Figure 1. CT imaging before (left) and after (right) Spontaneous Pneumothorax Conclusion: Spontaneous pneumothorax may be an unrecognized late complication of COVID-19 pneumonia. In hospitalized patients with acute respiratory decompensation, spontaneous pneumothorax should be considered as part of the differential diagnosis. Repeat chest imaging should be considered in these cases. Disclosures: All Authors : No reported disclosures